Implementasi Metode CRM (Customer Relationship Management) pada Sistem Informasi Website Nadu Screen Printing - Putro, Dwi Fany Julianto; Satriyawan, Haris (Universitas Batanghari Jambi, 2024)
This research aims to implement the CRM (customer relationship management) method on the Nadu Screen Printing website information system which is useful for simplifying customer orders and processing customer databases. This research uses the Agile software development method. The evaluation results with the System Usability Scale (SUS) show that this system meets the standards with a final score reaching 86.5 in the